Procedural outcomes of a novel underwater injection endoscopic mucosal resection technique for colorectal polyps ≥10 mm - Hirai, Yuichiro; Toyoshima, Naoya; Takamaru, Hiroyuki; Sekiguchi, Masau; Yamada, Masayoshi; Kobayashi, Nozomu; Sekine, Shigeki; Saito, Yutaka (Endoscopy, 2025)
It is uncertain whether underwater endoscopic mucosal resection (UEMR) enables resection of the submucosal tissue with sufficient margins for T1 colorectal cancer (CRC) because UEMR forgoes submucosal injection. Therefore, we developed a novel “underwater injection EMR” (UIEMR) method that combines submucosal injection with UEMR to obtain an adequate vertical margin.We retrospectively analyzed procedure-related outcomes of 135 consecutive lesions from patients who underwent UIEMR for ≥10-mm nonpedunculated colorectal polyps (median size 15 mm). The outcomes included the en bloc, R0, RX, and R1 resection rates, and adverse events. Additionally, the vertical margin distance of seven T1 CRCs was evaluated.En bloc resection was achieved in 127 lesions (94.1%). R0 and RX resections were observed in 92 (68.1%) and 42 lesions (31.1%), respectively, while R1 resection was seen in only one lesion (0.7%). There were two cases with adverse events (1.5%), both delayed bleeding. In T1 CRCs, all seven cases had free vertical margins, and the median vertical margin distance was 1140 µm (range 731–1570 µm).UIEMR safely demonstrated high success rates for en bloc resection, and potentially ensures a sufficient vertical margin. This technique might be an option, particularly for relatively small lesions concerning for T1 CRC, and deserves further study.